REPRESENTATION OF ISLAMIC FEMINISM IN ABIDAH EL KHALIEQY’S NOVELS - Dipa Nugraha; Suyitno Suyitno (LITERA, 2019)
The Indonesian literary tradition during the reform period was marked by the rise of female writers who raised the issue of feminism. Within the framework of locality and contextuality, the feminism movement echoed by female writers comes in diverse expressions. This study aims to describe the reference figures and issues of Islamic feminism that are represented in novels by Abidah El Khalieqy. This research uses a feminist literary criticism approach. The data sources of the research are three novels by Abidah El Khalieqiy, namely Perempuan Berkalung Sorban, Geni Jora, and Mataraisa. The technique used to gather feminist voices in the three novels is a close reading. The analysis was conducted using a descriptive qualitative method. The results of the study are as follows. First, Islamic feminist figures who were referred to by the feminism movement were Fatima Mernisi and Riffat Hassan. Fatima Mernisi is known as a misogonic hadith critic, while Riffat Hassan uses the hermeneutic principle in the interpretation of the Quran. Second, the issues of feminism represented are: the lives of women in the pesantren tradition, the position of women in the family, the view of normal sexual relations and relationships, and the interpretation of the hadiths and verses of the Qur'an relating to women. Islamic feminism voiced by Abidah El Khalieqy brings its own color compared to the Western feminism movement which refers to the concept of ecriture feminine. Keywords: Islamic Feminism, ecriture feminine, Indonesian literary history, politics of difference, intersectionality REPRESENTASI FEMINISME ISLAM DALAM NOVEL-NOVEL KARYA ABIDAH EL KHALIEQY AbstrakTradisi sastra Indonesia masa reformasi ditandai maraknya penulis perempuan yang mengangkat permasalahan feminisme. Dalam bingkai lokalitas dan kontekstualitas, gerakan feminisme yang digaungkan para penulis perempuan hadir dalam ekspresi yang beragam. Penelitian ini bertujuan mendeskripsikan tokoh rujukan dan persoalan feminisme Islam yang direpresentasikan dalam novel-novel karya Abidah El Khalieqy. Penelitian ini menggunakan pendekatan kritik sastra feminis. Sumber data penelitian adalah tiga novel karya Abidah El Khalieqiy, yaitu Perempuan Berkalung Sorban, Geni Jora, dan Mataraisa. Teknik yang dipakai untuk mengumpulkan suara-suara feminisme di dalam ketiga novel adalah pembacaan cermat (close reading). Analisis dilakukan dengan metode deskriptif kualitatif. Hasil penelitian sebagai berikut. Pertama, tokoh feminis Islam yang menjadi rujukan gerakan feminisme adalah Fatima Mernisi dan Riffat Hassan. Fatima Mernisi dikenal dengan kritik hadist misogonis, sedangkan Riffat Hassan dengan prinsip hermeneutika dalam tafsir Alquran. Kedua, persoalan feminisme yang direpresentasikan adalah: kehidupan perempuan dalam tradisi pesantren, kedudukan perempuan dalam keluarga, pandangan terhadap relasi dan hubungan seksual yang normal, dan tafsir terhadap hadist dan ayat Al-quran berkaitan dengan perempuan. Feminisme Islam yang disuarakan Abidah El Khalieqy membawa warna tersendiri dibandingkan dengan gerakan feminisme Barat yang merujuk pada konsep ecriture feminine. Kata kunci: feminisme Islam, ecriture feminine, sejarah sastra Indonesia, politik perbedaan, interseksionalitas.